Development of novel submerged anaerobic osmosis membrane bioreactor - Gu, Yangshuo (2015)
Forward Osmosis (FO) process is driven by osmotic energy, which is arisen from the osmotic pressure difference between the draw solution (high concentration) and the feed solution (low concentration) separated by a semi-permeable membrane. Combining anaerobic digestion with FO membrane to retain influent organic waste, this research aims to develop the integrated biological wastewater treatment technology: Anaerobic Osmosis-Membrane Reactor (AnOMBR). In the preliminary study, mixed organic fouling of the FO membrane in submerged mode was systematically investigated. Fouling behavior of cellulose triacetate (CTA) FO membrane and thin film composite (TFC) polyamide FO membranes were studied and compared. It was interesting to find under mild FO fouling conditions, TFC FO membranes could have greater fouling tendency as compared to CTA FO membranes due to their greater surface roughness. Although FO is believed to have superior fouling resistance in the AL-FS orientation, severe fouling could occur even at moderate flux levels, especially for TFC membranes or for unstable feed solutions. In this case, solution chemistries such as pH and presence of calcium ions posed remarkable effect on the cake layer composition due to the effect of foulant-foulant interaction(s); In contrast, the foulant composition was not strongly affected by the membrane type (CTA versus TFC) nor the testing mode (pressure-driven NF mode versus osmosis-driven FO mode). With the understanding of FO organic fouling mechanisms, a novel submerged AnOMBR utilizing CTA FO membrane in anaerobic bioreactor was developed and feasibility of using the AnOMBR to treat low-strength synthetic wastewater at mesophilic temperature was evaluated. Flux declined under the effect of both feed conductivity build-up and membrane fouling. Generally fouling on membrane was mild, while both organic fouling and inorganic scaling could still be observed at the edge of membrane. Bulk pH could be sustained within neutral to slightly alkaline due to the retention of alkalinity by FO membrane. The AnOMBR showed good and stable soluble chemical oxygen demand (sCOD) removal and perfect total phosphorous removal. However the removal of total nitrogen and ammonia still needed improvements. The elevated salt environment had marginal effect on bioactivity of methanogens and methane production of AnOMBR system was stable. Based on the promising results, the AnOMBR was operated at both mesophilic temperature and room temperature to compare the performance in terms of membrane flux level and mixed liquor conductivity, nutrient removal and methane production. At room temperature, the flux decreased and conductivity increased both at a slower speed than at mesophilic temperature. The membrane durability was also better and tap water cleaning was practical at room temperature with 90% flux recovery. At both temperatures, the AnOMBR showed good rejection to nutrients. However, at higher temperature, the nutrient concentration in supernatants was relatively lower, indicating the faster and efficient nutrient degradation by microbial at higher temperature. Methane production rate at mesophilic temperature was also significant higher than at room temperature.